UJI ORGANOLEPTIK YOGHURT DARI SUSU KAMBING PE (PERANAKAN ETAWA) DENGAN SUBSTITUSI KAYU MANIS (CINNAMOMUM VERUM) - Anwar, Muhammad Misbakhul; samur, salnan irba novaela; moeis, edya moelia (AVES: Jurnal Ilmu Peternakan, 2024)
This study evaluates the effect of adding cinnamon on the organoleptic quality of yogurt made from Peranakan Etawa (PE) goat milk. A Completely Randomized Design (CRD) method was used to manage variations between samples, and Analysis of Variance (ANOVA) was employed to determine significant differences between treatments. The findings revealed no statistically significant differences in organoleptic aspects such as visual appearance, aroma, color, and texture. However, panelists preferred yogurt with 2.5% cinnamon, indicating that this concentration may enhance the sensory appeal of yogurt by imparting a warm aroma and sweet flavor. The results suggest that while no significant differences were observed, the addition of cinnamon at this level can improve the overall sensory experience. Future research is recommended to explore a wider range of cinnamon concentrations and different types of cinnamon, as well as using a larger and more diverse panel to obtain more representative data.